Benchmarking the environmental performance of specialized milk production systems: selection of a set of indicators. (January 2017) - Mu, W.; van Middelaar, C.E.; Bloemhof, J.M.; Engel, B.; de Boer, I.J.M.
Highlights: Indicators to benchmark the environmental performance of dairy farms were selected. N surplus, P surplus, energy use and land use can be used as a proxy for benchmarking. Global warming, acidification and eutrophication potential were eliminated. Selected indicators are representative, easy to collect and easy to interpret. Abstract: Dairy production across the world contributes to environmental impacts such as eutrophication, acidification, loss of biodiversity, and use of resources, such as land, fossil energy and water. Benchmarking the environmental performance of farms can help to reduce these environmental impacts and improve resource use efficiency. Indicators to quantify and benchmark environmental performances are generally derived from a nutrient balance (NB) or a life cycle assessment (LCA). An NB is relatively easy to quantify, whereas an LCA provides more detailed insight into the type of losses and associated environmental impacts. In this study, we explored correlations between NB and LCA indicators, in order to identify an effective set of indicators that can be used as a proxy for benchmarking the environmental performance of dairy farms. We selected 55 specialised dairy farms from western European countries and determined their environmental performance based on eight commonly used NB and LCA indicators from cradle-to-farm gate. Indicators included N surplus, P surplus, land use, fossil energy use, global warming potential (GWP), acidification potential (AP), freshwater eutrophication potential (FEP) and marine eutrophication potential (MEP) for 2010. All indicators are expressed per kg of fat-and-protein-corrected milk. Pearson and Spearman Rho's correlation analyses were performed to determine the correlations between the indicators. Subsequently, multiple regression and canonical correlation analyses were performed to select the set of indicators to be used as a proxy. Results show that the set of selected indicator, including N surplus, P surplus, energy use and land use, is strongly correlated with the eliminated set of indicators, including FEP (r = 0.95), MEP (r = 0.91), GWP (r = 0. 83) and AP (r = 0.79). The canonical correlation between the two sets is high as well (r = 0.97). Therefore, N surplus, P surplus, energy use and land use can be used as a proxy to benchmark the environmental performance of dairy farms, also representing GWP, AP, FEP and MEP. The set of selected indicators can be monitored and collected in a time and cost-effective way, and can be interpreted easily by decision makers. Other important environmental impacts, such as biodiversity and water use, however, should not be overlooked.